RETRACTED: Model Penyelesaian Tindak Pidana Penebangan Hutan Mangrove Melalui Hukum Adat di Kecamatan Mandah Kabupaten Indragiri Hilir Provinsi Riau - Erdianto; Ferawati; Imam Aliani Putra (Jurnal Hukum Lex Generalis, 2021)
The manuscript entitled "Model for Solving Mangrove Forest Logging Through Customary Law in Mandah District of Indragiri Hilir Regency of Riau Province" published in Lex Generalis Law Journal Vol.2 No.11 (November 2021) on the link https://ojs.rewangrencang.com/index.php/JHLG/article/view/75 to the Editor's search has a main substance similarity with the manuscript that has been published previously in another journal, namely Riau Law Journal Vol.4 No.2 (2020) on the https://rlj.ejournal link. unri.ac.id/index.php/RLJ/article/view/7856. Based on that finding, the editorial decide to retract this manuscript. The announcement of the retraction of this manuscript can be accessed via the following link: https://ojs.rewangrencang.com/index.php/JHLG/article/view/268.